Remarks on weak amenability of hypergroups - Alaghmandan, Mahmood (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 512.5We study the existence of multiplier (completely) bounded  approximate identities for the Fourier algebras of some classes of  hypergroups. In particular, it is shown that, the hypergroups from a large class of commutative hypergroups are weakly amenable with the Cowling–Haagerup constant $1$.  As a corollary, we  answer an open question of Eymard about Jacobi hypergroups. We also characterize the existence of  bounded approximate identities for the hypergroup Fourier algebras of spherical hypergroups.